Nanocapsules for the co-delivery of selol and doxorubicin to breast adenocarcinoma 4T1 cells in vitro. (17th November 2018) - Ganassin, Rayane; Merker, Carolin; Rodrigues, Mosar Corrêa; Guimarães, Nayara Felipe; Sodré, Carine Sampaio Cerqueira; Ferreira, Queila da Silva; da Silva, Sebastião William; Ombredane, Alicia Simalie; Joanitti, Graziella Anselmo; Py-Daniel, Karen Rapp; Zhang, Juan; Jiang, Cheng-Shi; et al.
Abstract: Nanocapsules (NCS-DOX) with an oily core of selol and a shell of poly(methyl vinyl ether-co-maleic anhydride) covalently conjugated to doxorubicin were developed. These nanocapsules are spherical, with an average hydrodynamic diameter of about 170 nm, and with negative zeta potential. NCS-DOX effectively co-delivered the selol and the doxorubicin into 4T1 cells and changed the intracellular distribution of DOX from the nuclei to the mitochondria. Moreover, a significantly increased cytotoxicity against 4T1 cells was observed, which is suggestive of additive or synergic effect of selol and doxorubicin. In conclusion, PVM/MA nanocapsules are suitable platforms to co-deliver drugs into cancer cells.